EFFECTIVENESS OF MUSIC THERAPY ON ANXIETY AND B-ENDORPHIN LEVELS IN PRIMIGRAVIDA DURING THE THIRD STAGE OF PREGNANCY - Surya Dayyana; Suryono Suryono; Melyana Nurul Widyawati; Syarief Thaufik Hidayat (Belitung Nursing Journal, 2017)
Objective: To examine the effectiveness of music therapy on anxiety and β-endorphin levels in primigravida during the third stage of pregnancy. Methods: This was a quasi-experimental study with pretest-posttest control group design. The research was conducted in December 2016 - January 2017. There were 39 respondents selected using purposive sampling technique, which 13 assigned in the experiment group 1 (music therapy with a sound pressure of 40 dB), experiment group 2 (music therapy with a sound pressure of 62 dB) and control group (health counseling). Anxiety levels were measured using the HARS (Hamilton Anxiety Rating Scale), and β-endorphin hormone levels were measured using ELISA (Enzyme-Linked Immunosorbent Assay) method. Data were analyzed using Paired t-test, One-Way ANOVA test with post-hoc Bonferroni, and Kruskal Wallis test with post-hoc Mann Whitney. Results: Findings revealed that there was a decrease of the mean of anxiety levels in the experiment group 1 from 31.92 (pretest) to 24.69 (posttest), and the experiment group 2 from 34.54 (pretest) to 25 (posttest) with p-value <0.05. There was an increase of the mean of β-Endorphin levels in the experiment group 1 from 53.63 (pretest) to 63.24 (posttest), and the experiment group 2 from 48.55 (pretest) to 64.9 (posttest) with p-value <0.05. However, there was no effect of counseling in the control group on anxiety levels (p=0.413) and β-Endorphin levels (p= 0.394). Conclusion: Music therapy is effective in reducing anxiety levels and increasing β-endorphin levels. Thus, music therapy can be used as an alternative treatment for pregnant mothers at home who experienced anxiety.